Introduction to the Editor's Column: Surveying Our Spacious Field - Peterson, Lesley (Journal of Juvenilia Studies, 2026)
This essay introduces the Editor's Column of JJS 7.2, which brings together six short papers on the theme, "Surveying Our Spacious Field." I explain that these papers are all based on talks given in June 2025 during the interdisciplinary symposium “Discovering, Working in, and Creating Collections” that was held at The University of North Carolina at Chapel Hill and organized by Laurie Langbauer.